High‐Resolution Microendoscope Images of Middle Ear Cholesteatoma and Surrounding Tissue: Evaluation of Interobserver Concordance. (23rd August 2013) - Bradley, James A.; Jiang, Nancy; Levy, Lauren L.; Richards‐Kortum, Rebecca; Sikora, Andrew; Smouha, Eric E.
Abstract : Objectives: High‐resolution microendoscopy (HRME) has great potential to detect residual cholesteatoma in patients. This study investigated how accurately otolaryngologists could differentiate between images obtained with HRME of ex vivo cholesteatoma specimens and surrounding middle ear epithelium. Methods: Cholesteatoma and surrounding middle ear epithelium were resected from patients. Tissues were stained with a contrast agent, proflavine. The HRME was placed directly on each specimen, and images were captured. Specimens were sent for standard histopathology and were subsequently compared with HRME images. Images were evaluated for quality control, and a training set was assembled. After viewing training images, 8 otolaryngologists without prior cholesteatoma HRME experience reviewed and classified test images. Results: Ten cholesteatoma and 9 middle ear specimens were collected, of which 17 representative cholesteatoma and 19 middle ear epithelium images were extracted for a testing set. Qualitative analysis for concordance between HRME images and histological images yielded a strong correlation between modalities. The mean accuracy of all reviewers in correctly identifying images was 95% [95% confidence interval [CI]: 92, 98]. The sensitivity to correctly detect cholesteatoma images was 98% [95% CI: 93, 100], and the specificity was 92% [95% CI: 87, 97]. The Fleiss kappa inter‐rater reliability score was 0.83 [95% CI: 0.77, 0.89]. Conclusions: Medical professionals can quickly be trained to accurately distinguish between HRME images of cholesteatoma and normal middle ear epithelium, both of which have distinct imaging characteristics. Real‐time HRME optical imaging can potentially improve the results of otologic surgery by allowing for extirpation of cholesteatomas while eliminating residual disease.